Minat Kunjungan Mahasiswa Tingkat II Kongregasi Serikat Maria Montfortan Ke Perpustakaan Sekolah Tinggi Filsafat Teologi Widya Sasana - Kristoforus Juliano Ilham; Antonius Denny Firmanto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The background of this research is to review the interests of second-level students of the Societas Maria Montfortana (SMM) congregation when visiting the Widya Sasana School of Philosophy of Theology (STFT) library. The goal to be achieved is to find out to what extent second-level students of the SMM congregation have an interest in visiting the STFT Widya Sasana library. The interest of the second year students of the SMM congregation was seen based on the frequency of visiting the library. The research method used here is a quantitative research method in the form of an ordinal questionnaire given to second year students of the SMM congregation. This questionnaire technique helps to obtain research data that will be measured numerically. The results of this study will reveal that the activeness of visiting the STFT Widya Sasana library is proof that second-level students of the SMM congregation have an interest in visiting the STFT Widya Sasana library.